Opposing seasonal trends in source water and sugar dampen intra‐annual variability in tree rings oxygen isotopes - Szejner, Paul; Tang, Yu; Angove, Charlotte; Schiestl‐Aalto, Pauliina; Sahlstedt, Elina; Young, Giles; Nelson, Daniel B.; Kahmen, Ansgar; Saurer, Matthias; Rinne‐Garmston, Katja T. (John Wiley & Sons, 2025)
Variations of oxygen isotopes δ18O in tree rings provide critical insights into past climate and tree physiological processes, yet the mechanisms shaping the intra-annual δ18O signals remain incompletely understood. To address this gap, we investigated how seasonal changes in source water, leaf water, and sugars influence δ18O recorded along the tree rings of Pinus sylvestris in Finland.We conducted a seasonal analysis measuring δ18O from needle water, source water, and phloem sugars and investigated the fraction of oxygen isotope exchange during wood formation.We found that seasonal δ18O amplitudes are significantly reduced from leaf water to tree rings, driven by opposing seasonal patterns in increasing source water δ18O and decreasing evaporative enrichment as relative humidity increases. Additionally, the isotope exchange between source water and phloem sugars further dampens seasonal δ18O signals in the rings.Our findings show that oxygen isotope exchange is critical in shaping δ18O signals, influencing the role of source water and relative humidity recorded on intra-annual resolution. This refined understanding helps interpret tree physiological responses under changing conditions and improves climate reconstructions based on tree rings using intra-annual resolution.
Keywords: boreal forests; high-resolutiondendrochronology; needle sugars; phloemsugars; post-photosynthetic fractionation; proxy records; stable isotopes